Settler colonialism, race, and the law : why structural racism persists - Saito, Natsu Taylor (New York : New York University Press, 2020)
'Settler Colonialism, Race, and the Law' begins from the premise that the United States is neither postracial nor postcolonial. Using the lens of settler colonial theory, it attributes the origins and persistence of racialized inequities in the United States to the prerogatives asserted by its predominantly Angloamerican founders to appropriate Indigenous lands and resources, to profit from the labour of voluntary and involuntary migrants, and to ensure that all people of colour remain 'in their place.' This text assesses the experiences of American Indians, African Americans, Latina/os, and Asian Americans to the present day in terms of the strategies utilized by the settlers to accomplish these ends.
Also issued in print: 2020.
Includes bibliographical references and index.
Specialized.
Description based on online resource; title from home page (viewed on August 3, 2020).
Keywords: Race discrimination -- Law and legislation -- United States -- History; Minorities -- Legal status, laws, etc. -- United States -- History; Racism -- United States -- History; United States -- Race relations -- History; United States -- Colonization -- History; Indigenous peoples -- Legal status, laws, etc. -- United States -- History; Decolonization -- United States -- History; United States -- Territorial expansion; Society; Society & culture: general